2018
DOI: 10.1021/acsanm.8b01745
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Electron Mobility of ZnO-Based Transparent Conductive Films Deposited by Open-Air Methods for Enhanced Sensing Performance

Abstract: The development of open-air, high-throughput, low-cost thin film fabrication techniques has immense potential and interest in optoelectronics. However, the oxygen-rich atmosphere associated with such processes can have detrimental effects on the electrical properties of the deposited films. An example of this is found in materials based on ZnO, for which atmospheric processing results in low mobility values. This stems mainly from adsorbed oxygen species at the grain boundaries, which limit carrier transport. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…It has previously been shown that annealing ZnO films in air results in a reduction in the concentration of oxygen vacancies, or an increase in oxygen interstitial trap states, and hence a decrease in the available charge carriers 51 . As noted earlier, it has also been reported that oxygen tends to accumulate at the grain boundaries of ZnO-based films, slowing transport of charges from one grain to another as the electrons must tunnel through this barrier 39,40 . www.nature.com/scientificreports/ This effect leads to an increase in film resistance of a couple orders of magnitude, and is particularly noted in AP-SALD films.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It has previously been shown that annealing ZnO films in air results in a reduction in the concentration of oxygen vacancies, or an increase in oxygen interstitial trap states, and hence a decrease in the available charge carriers 51 . As noted earlier, it has also been reported that oxygen tends to accumulate at the grain boundaries of ZnO-based films, slowing transport of charges from one grain to another as the electrons must tunnel through this barrier 39,40 . www.nature.com/scientificreports/ This effect leads to an increase in film resistance of a couple orders of magnitude, and is particularly noted in AP-SALD films.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, the outer substrate positions are likely to be exposed to more oxygen from the surrounding atmosphere, whereas the central portion of the substrate remains better isolated from the external environment. It has recently been reported that oxygen exposure limits the mobility and hence conductivity of ZnO-based films deposited by open-air methods via barrier formation at the grain boundaries, such that this may also contribute to the higher resistances observed at the outer substrate positions 39 , 40 . The ZnO photoluminescence spectra at different positions on the substrate can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TiO 2 films were deposited using a home‐made AP‐SALD [ 44 ] using TiCl 4 as titanium precursor and water as oxygen precursor. The deposition was performed at a substrate temperature of 150 °C and in the open air.…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth mentioning that ZnO‐based TCOs may not be the best candidates for high temperature applications, since ZnO tends to absorb oxygen species in the grain boundaries, which has a detrimental effect on mobility, as explained and modelled recently. [ 19 ] It has been shown that the absorption of oxygen species increases rapidly with temperature, [ 134 ] thus most likely limiting the applications of THs based on AZO.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 99%